2015
DOI: 10.1016/j.redox.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant therapy for treatment of inflammatory bowel disease: Does it work?

Abstract: Oxidative stress (OS) is considered as one of the etiologic factors involved in several signals and symptoms of inflammatory bowel diseases (IBD) that include diarrhea, toxic megacolon and abdominal pain. This systematic review discusses approaches, challenges and perspectives into the use of nontraditional antioxidant therapy on IBD, including natural and synthetic compounds in both human and animal models. One hundred and thirty four papers were identified, of which only four were evaluated in humans. Some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
224
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(238 citation statements)
references
References 297 publications
(324 reference statements)
7
224
0
7
Order By: Relevance
“…Another prior study revealed that TQ ameliorates the renal proliferative response due to mercury exposure in rats. TQ decreases histological damage such as renal cell apoptosis and proliferative reactions (26). While many studies have suggested that TQ is a nephroprotective agent, in the present study we further suggest that it has a higher nephroprotective effect than either NAC or silymarin.…”
Section: Discussionsupporting
confidence: 58%
“…Another prior study revealed that TQ ameliorates the renal proliferative response due to mercury exposure in rats. TQ decreases histological damage such as renal cell apoptosis and proliferative reactions (26). While many studies have suggested that TQ is a nephroprotective agent, in the present study we further suggest that it has a higher nephroprotective effect than either NAC or silymarin.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, the presence of colonic ulcers, as a consequence of lipid peroxidation and protein damage and development of cancer, is due to DNA damage [4]. However, the cause of these symptoms and clinical manifestations is heterogeneous, varying according to the UC level: mild, moderate, or severe.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, lipoic acid (LA) and N- acetylcysteine (NAC) stand out, which have been tested separately in UC [4], and in combination for other clinical conditions [11, 12], with positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants can reduce inflammation via the inhibition of pro-inflammatory mediators, as well as the increase of the anti-inflammatory mediator production (Costa et al 2013;Moura et al 2015).…”
Section: Introductionmentioning
confidence: 99%